Does Imagery Ability Matter for the Relationship Between Temperament and Self-Confidence in Team and Individual Sport Disciplines? - Budnik-Przybylska, Dagmara; Huzarska, Izabela; Karasiewicz, Karol (Frontiers in Psychology, 2022)
The main purpose of our study was to investigate the relationship among temperamental traits, general tendency to use imagery and self-confidence in sport. The specific aim was to verify if general imagery mediates the relationship between temperament and self-confidence in sport, but also with respect to individual and team sport disciplines. The study involved 144 athletes aged 19 to 25 years (75 males and 69 females) with different lengths of training (from 1 month to 18 years) and presenting different sport levels: international (n=12), national (n=46) and recreational (n=86). They also represented individual (n=73) and team (n=68) sports. The participants completed The Imagination in Sport Questionnaire (ISQ), Trait Sports Confidence Inventory (TSCI - PL) and The EAS Temperament Questionnaire. Results indicate that self-confidence is explained in about 13% by temperament and general imagery, but only general imagery (b=,22; p<,05), and negative axes of the temperament - emotionality (b=-,26; p<,05). The test of indirect effect of the negative axes of the temperament on self-confidence through general imagery conducted by Preacher and Hayes bootstrapping procedure revealed significant mediation [b=,37; CI95=(,09;.68); R2Med=,46] suggesting that about 46% of variance explained in self-confidence by emotionality is related to general imagery. The other 3% of variance explained in self-confidence by the positive temperament axes is related to general imagery, however it was insignificant. The general imagery explains the relation between emotionality and self-confidence only in individual sports athletes.